TAKAFUL IS AN INVESTMENT ACTIVITY - Iskandarov Muhammadali; Umarov Alseit (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, takaful is considered as an alternative to conventional insurance. Takaful is said to be an advantage over conventional insurance and the most alternative risk prevention option for many Muslim countries. An example of this is the vakala model of takaful.